2016
DOI: 10.1002/acp.3278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Daylight Saving Time on Punctuality for Medical Appointments

Abstract: We studied the effect of the switch from daylight saving time to winter time on punctuality for medical appointments, thus allowing us to investigate the role of dynamic and analytic modes of time management in time-based prospective memory tasks. Insofar as some authors assume that the dynamic mode of time management is based on rhythms, we hypothesised that the switch from daylight saving time would cause more disturbances when participants' everyday activity had a weak temporal structure. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…Although the study and did not address the causes of the DST effect directly, the observed changes in DNA rates suggests that changes in sleep patterns may have an impact on missed appointments. A similar trend has also been observed when measuring punctuality, with patients arriving earlier for appointments following transitions out of DST (Valax et al 2016).…”
Section: Discussionsupporting
confidence: 68%
“…Although the study and did not address the causes of the DST effect directly, the observed changes in DNA rates suggests that changes in sleep patterns may have an impact on missed appointments. A similar trend has also been observed when measuring punctuality, with patients arriving earlier for appointments following transitions out of DST (Valax et al 2016).…”
Section: Discussionsupporting
confidence: 68%